1998
DOI: 10.1023/a:1006919009621
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Understanding the genetic mechanisms involved in resistance to antifungal agents is important in the fight against pathogenic fungi. In the present investigation we studied a strain of the model fungus Aspergillus nidulans which presents resistance to tioconazole and behaves as the wild strain in the presence of other azole derivatives. Genetic analysis revealed that this resistance is due to a mutation in a single gene located on chromosome II, closely linked to the allele responsible for resistance to acrifl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Genes associated with acriflavine resistance have been identified in different organisms. Molecular cloning of these genes revealed that many of them encode multidrug resistance pumps that transport acri-flavine out of the cell (De Rossi et al, 1998 ;Masaoka et al, 2000 ;Nakaune et al, 1998 ;Pereira et al, 1998). Inactivating mutations in these transporter genes lead to acriflavine sensitivity (Ma et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Genes associated with acriflavine resistance have been identified in different organisms. Molecular cloning of these genes revealed that many of them encode multidrug resistance pumps that transport acri-flavine out of the cell (De Rossi et al, 1998 ;Masaoka et al, 2000 ;Nakaune et al, 1998 ;Pereira et al, 1998). Inactivating mutations in these transporter genes lead to acriflavine sensitivity (Ma et al, 1994).…”
Section: Discussionmentioning
confidence: 99%